2022
DOI: 10.3390/jpm12081238
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mediterranean Diet Combined with CrossFit Training on Trained Adults’ Performance and Body Composition

Abstract: CrossFit is a high-intensity training discipline increasingly practiced in recent years. Specific nutritional approaches are usually recommended to maximize performance and improve body composition in high-intensity training regimens; notwithstanding, to date there are no targeted nutritional recommendations for CrossFit athletes. The Mediterranean Diet (MD) is a diet approach with a well-designed proportion of macronutrients, using only available/seasonal food of the Mediterranean area, whose health benefits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…It involves a moderate intake of dairy products, primarily cheese, fish, and poultry, while limiting the consumption of red and processed meats. Studies reported that MD provides athletes with a sufficient supply of carbs, which are suitable for enhancing recovery and optimizing the performance of CrossFit athletes, in addition to bioactive ingredients [ 160 ].…”
Section: Optimal Nutrition For Recoverymentioning
confidence: 99%
“…It involves a moderate intake of dairy products, primarily cheese, fish, and poultry, while limiting the consumption of red and processed meats. Studies reported that MD provides athletes with a sufficient supply of carbs, which are suitable for enhancing recovery and optimizing the performance of CrossFit athletes, in addition to bioactive ingredients [ 160 ].…”
Section: Optimal Nutrition For Recoverymentioning
confidence: 99%
“…For performance, the MedDiet has been touted to help athletes from a performance and body composition standpoint, as it provides nutritional support for their training and athletic demands with a low inflammatory index. During an 8-week MedDiet intervention, CrossFit athletes had significant increases in squat jump performance, power, muscular endurance, and anaerobic power [ 22 ]. Additionally, athletes saw increases in CrossFit-specific maneuvers and performance [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…During an 8-week MedDiet intervention, CrossFit athletes had significant increases in squat jump performance, power, muscular endurance, and anaerobic power [ 22 ]. Additionally, athletes saw increases in CrossFit-specific maneuvers and performance [ 22 ]. The athletes in the dietary group showed increased performance during the chin-up test to exhaustion, i.e., from 11 repetitions to 13 repetitions [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, whole-body bone mineral density, lean soft mass, and %FM differ among CrossFit® athletes according to the amount of training [ 6 ]. On the other hand, an 8-weeks Mediterranean Diet plan did not affect BC in well trained CrossFit® athletes/practitioners [ 7 ], although it may positively affect CrossFit® performance.…”
Section: Introductionmentioning
confidence: 99%